Certain issues of teaching the German language as the Second Foreign Language in Technical Higher Educational Institution - I. Chechetka, Valentina (2019)
Formulation of the problem. The article considers various approaches and methods for teaching German as the second foreign language offered by domestic and foreign scientists testifying to the need for additional comprehension and refinement of the main principles for teaching German as the second foreign language after learning English. The linguistic characteristics of English and German are analyzed at the phonetic, grammatical and lexical levels.Results. The theoretical analysis of the factors for teaching and learning German as the second language is given. It allowed us to reveal the following principles as fundamental ones: the principle of support and comparative connection with the first foreign and native languages, the principle of individualization of teaching, as well as the cognitive principle. It was found out how to approach the organization of the content of teaching, forms and methods of teaching so that students acquire explicit and implicit experience in the formation and improvement of teaching strategies. The study proved that parallel learning of the English and German languages has special advantages for learners based on the linguistic similarity of these two languages.Conclusions. The theoretical and practical analysis of the factors for teaching and learning German as the second language allowed us to reveal the following principles as fundamental ones: the principle of support and comparative connection with the first foreign and native languages, the principle of individualization of teaching, as well as the cognitive principle. The analysis allowed us to understand how to approach the organization of the content of training, forms and methods of teaching, so that students acquired explicit and implicit experience in the formation and improvement of teaching strategies. The study also clearly demonstrated that the parallel learning of the English and German languages had special advantages for learners, based on the linguistic similarity of these two languages.